2017
DOI: 10.1016/j.snb.2017.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of urinary microRNAs via sulfonamide-bound antisense hybridisation

Abstract: HighlightsA modified glassy carbon electrochemical sensor for microRNAs was developed.The electrode allowed detection of femtomolar concentrations of miR-21.The method was applied to detection of urinary miR-21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…We are still beginning to understand the role of non-coding RNAs. Currently, the techniques used for their isolation and analyses (including Northern blotting, RT-qPCR, microarray, surface plasmon resonance and fluorescence-based techniques [ 103 ]), despite being technically advanced, do not provide results rapidly. Due to the fact that RNA-based sequences are quite small, their analysis frequently requires the conversion of transcripts into a pool of cDNAs constituting the sequencing library.…”
Section: Mirna Ncrna Lncrna and Lincrna Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…We are still beginning to understand the role of non-coding RNAs. Currently, the techniques used for their isolation and analyses (including Northern blotting, RT-qPCR, microarray, surface plasmon resonance and fluorescence-based techniques [ 103 ]), despite being technically advanced, do not provide results rapidly. Due to the fact that RNA-based sequences are quite small, their analysis frequently requires the conversion of transcripts into a pool of cDNAs constituting the sequencing library.…”
Section: Mirna Ncrna Lncrna and Lincrna Biomarkersmentioning
confidence: 99%
“…However, we believe that in several years, the results of the most significant findings will be translated into diagnostic tests, perhaps in manner less simple than performing dipstick tests, but nonetheless less complicated and time- and effort-consuming than present methods. Smith et al [ 103 ] made a step in this direction designing a method of electrochemical detection of miRNAs in a urine sample which requires minimal liquid handling in a straightforward dipstick-style test. Moreover, in their method urine sample can be small and there is no need for extensive miRNA extraction procedures as well as toxic and expensive reagents.…”
Section: Mirna Ncrna Lncrna and Lincrna Biomarkersmentioning
confidence: 99%
“…However, miRs appear to be ideal future biomarkers for urinary analysis because of their presence and stability in urine [ 19 ], their relatively easy detectability (by qRT-PCR), their stability even after freeze-thaw cycles, and their specificity to tissue or disease states. Therefore, it is noteworthy that Smith et al [ 74 ] reported a promising approach to detect urinary miRs with high sensitivity via sulfonamide-bound antisense hybridisation. The authors claim that this method has several significant advantages over circulating biomarker analysis including safety, cost, speed, and ease of conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Unspecific protein adsorption and matrix effects appear when using patient samples with label-free techniques. In an impedimetric hybridization-based biosensor for miRNA-21 reporting fM LOD, urine was digested with proteinase K and then filtrated (Smith et al, 2017). That way, an antifouling strategy to protect the surface is unnecessary while miRNA integrity is preserved, though direct detection is not viable.…”
Section: Dna-based Yellow Diagnosticsmentioning
confidence: 99%